Kritik atas Pemikiran Humanisme Pendidikan John Dewey - Fadhlullah, Irfan (el Buhuth: Borneo Journal of Islamic Studies, 2019)
Education is one of a container to get science. The various education stated by the scientists a western education has a decisive output students. Because in the concept of education has a philosophy that used as basis in developing their activities in the direction of education were. Islamic have the cincept of tarbiyah of course also has the basis of the muslim scholar ever incised ink gold in his days. The concept of Islamic education did not refuse modern concept as has beeb thriving now, but in the concept of Islamic education is self have whose distinctiveness not necessarily owned by the concept of a western education. Therefore in order to criticize the concept of education, the writer uses a qualitative descriptive approach with the type of library research. This type of library research is done by collecting some literature from books, journal and previous research result that have a theme related to the purpose of enriching references.